Horror 2.0 (On Demand): The Digital Convergence of Horror Film Culture. (July 2014) - Tompkins, Joe
This article examines the horror movie industry's mobilization of web content and digital distribution outlets, such as video-on-demand (VOD), and how specific fan practices get encoded into business models shaping web 2.0 strategies. Specifically, it examines the emergence of the multiplatform brand Fearnet, a joint cable channel, website, and VOD service owned by Comcast, Lionsgate, and Sony Pictures Entertainment. It argues that the service, which features horror movies taken from the Sony/MGM library and includes a host of interactive features, not only illustrates the changing impact of new media technologies on film distribution but also the growing industrial utility of VOD services for both cable and film industries. By relying on subcultural practices and discourses specific to horror fandom, digital services like Fearnet act as branded media conduits for the various markets and commerce that sustain niche-oriented categories of horror as a commodified experience.